Socioeconomic Differences in Tobacco Smoking in Italy: Is There an Interaction between Variables?. (12th March 2012) - Semyonov, Leda; Iarocci, Gianluca; Boccia, Antonio; La Torre, Giuseppe
Abstract : Objectives . To assess the influence of sociodemographic factors on smoking habits in Italy and if an interaction exists between these variables. Methods . Data from the national survey "Health Conditions and Healthcare Services Use" in 2005 were used. The independent association between tobacco smoking and sociodemographical variables was assessed using logistic regression analysis. Interactions between variables were investigated calculating the synergism index (SI). Results . Sample population consists of 109.829 subjects (over 15 years). 21.9% are current and 21.8% are former smokers. Current smokers are mostly 45–54-years old males, from Central Italy, unemployed, divorced or separated but having a good health status without chronic medical conditions. Ever smokers are mostly 45–54 years old males, from Northeast Italy, unemployed, with chronic conditions. People with a university degree and with a good household income have the lowest OR for both conditions. A synergistic effect was found between marital status and educational level (for ever smokers SI = 1.96; for current smokers SI = 1.67). Conclusions . Smoking is prevalent in lower socioeconomic groups and there is the strong need to increase social, economic and cultural capital in order to reduce it.